2008
DOI: 10.1177/1087054707314028
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Impairment in the Diagnosis of ADHD

Abstract: Symptoms and impairment are related yet distinct constructs that should be measured independently to determine the presence of ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 23 publications
(19 reference statements)
3
73
0
1
Order By: Relevance
“…Previous studies of school-aged children have found that ADHD symptoms explain about 25% to 30% of variance in impairment (9)(10)(11), which is quite similar to our findings of less than 30%. A pertinent question is of course which other factors determine impairment in children with ADHD, but studies specifically addressing these issues are largely missing.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies of school-aged children have found that ADHD symptoms explain about 25% to 30% of variance in impairment (9)(10)(11), which is quite similar to our findings of less than 30%. A pertinent question is of course which other factors determine impairment in children with ADHD, but studies specifically addressing these issues are largely missing.…”
Section: Discussionsupporting
confidence: 92%
“…Given its importance in the referral for ADHD and its relevance in treatment planning, it follows that such information could also be helpful in the assessment process. For example, recent studies suggest that consideration of impairment as a separate construct enhances the accuracy of diagnosis [9,16].…”
Section: Assessment Of Adhdmentioning
confidence: 99%
“…Lack of clarity of what impairment is (or how it can be measured) or even the assumption that symptoms and impairment are equivalent dimensions may underlie the inconsistent use of impairment measures 4,5 . Overlooking impairment leads to false positive diagnoses and overestimates of prevalence rates 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the correlation between ADHD symptoms and impairment may be only moderate 5 , it is necessary for the clinician to minimize as much as possible any potentially interfering aspects during consultation. b) Although research data does not support the idea that ADHD is a cultural construct 15 , we and others have suggested 16 that there is a wide variation in beliefs related to ADHD among countries -both cultural and historical.…”
Section: Introductionmentioning
confidence: 99%